Aquaculture Reuse Water, Genetic Line, and Vaccination Affect Rainbow Trout (Oncorhynchus mykiss) Disease Susceptibility and Infection Dynamics - Everson, Jeremy L.; Jones, Darbi R.; Taylor, Amy K.; Rutan, Barb J.; Leeds, Timothy D.; Langwig, Kate E.; Wargo, Andrew R.; Wiens, Gregory D. (Frontiers in Immunology, 2021)
Infectious hematopoietic necrosis virus (IHNV) and Flavobacterium psychrophilum are major pathogens of farmed rainbow trout. Improved control strategies are desired but the influence of on-farm environmental factors that lead to disease outbreaks remain poorly understood. Water reuse is an important environmental factor affecting disease. Prior studies have established a replicated outdoor-tank system capable of varying the exposure to reuse water by controlling water flow from commercial trout production raceways. The goal of this research was to evaluate the effect of constant or pulsed reuse water exposure on survival, pathogen prevalence, and pathogen load. Herein, we compared two commercial lines of rainbow trout, Clear Springs Food (CSF) and Troutex (Tx) that were either vaccinated against IHNV with a DNA vaccine or sham vaccinated. Over a 27-day experimental period in constant reuse water, all fish from both lines and treatments, died while mortality in control fish in spring water was <1%. Water reuse exposure, genetic line, vaccination, and the interaction between genetic line and water exposure affected survival (P<0.05). Compared to all other water sources, fish exposed to constant reuse water had 46- to 710-fold greater risk of death (P<0.0001). Tx fish had a 2.7-fold greater risk of death compared to CSF fish in constant reuse water (P<0.001), while risk of death did not differ in spring water (P=0.98). Sham-vaccinated fish had 2.1-fold greater risk of death compared to vaccinated fish (P=0.02). Both IHNV prevalence and load were lower in vaccinated fish compared to sham-vaccinated fish, and unexpectedly, F. psychrophilum load associated with fin/gill tissues from live-sampled fish was lower in vaccinated fish compared to sham-vaccinated fish. As a result, up to forty-five percent of unvaccinated fish were naturally co-infected with F. psychrophilum and IHNV and the coinfected fish exhibited the highest IHNV loads. Under laboratory challenge conditions, co-infection with F. psychrophilum and IHNV overwhelmed IHNV vaccine-induced protection. In summary, we demonstrate that exposure to reuse water or multi-pathogen challenge can initiate complex disease dynamics that can overwhelm both vaccination and host genetic resistance.